(Role of Hadhrami Arab in political influence of the Johore Sultanate in the early 20 the century A.D) Peranan Arab Hadhrami di dalam mempengaruhi politik Istana Kerajaan Johor pada awal abad ke 20M - Nurulwahidah Fauzi (Institut Kajian Rantau Asia Barat, 2012)
Throughout the 19 A.D, historical facts has shown that more than three million Arab's migrated to the country abroad. Fred through his study classifies four types of migrations performed by this colony, two of which featured the migration of Hadhramaut Yemen Arab society. The colony who claimed as a descendants of the Prophet, are famous through diaspora migration begin as early as 12 A.D with the trade transactions to India, East Africa in 1250 A.D and Malay Archipelago within 13 A.D afterward. Their migration are not only change their standard of living, even indirectly they generate a transformation in many aspects involving economic, politics, Islamic administration and social activities. The primary and secondary sources found that the Arab Hadhrami was elected to a Islamic Administration in Johore Government as early as the era of Sultan Abu Bakar. This occurs through the influence of good relations between Johore Palace and Ottoman Empire. Historical record that lasted a result of this relationship saw the appointment of six prominent figures from Arab Hadhrami started from 1896-1981M.